2018
DOI: 10.1177/1687814018783636
|View full text |Cite
|
Sign up to set email alerts
|

The environmental navigation using geometric virtual reality

Abstract: This article explores the construction of a geometric virtual reality platform for the environmental navigation. Nonpanoramic photos and wearable electronics with Bluetooth wireless transmission functions are used to combine the user's actions with the virtual reality environment in a first-person virtual reality platform. The 3ds Max animation software is used to create three-dimensional models of real buildings. These models are combined with the landscape models in Unity3d to create a virtual campus scene t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The purpose of this study was to use an eight-bit RISC microcontroller chipset to detect the actions of game players and use motion-sensing interaction technology to control 3D character models in VR. A similar study (8) showed the construction of a geometric VR platform for environmental navigation, where non-panoramic photos and wearable electronics with Bluetooth wireless transmission functions were used to combine the user's actions with the VR environment in a first-person VR platform.…”
Section: Functional Tests and Experiments Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this study was to use an eight-bit RISC microcontroller chipset to detect the actions of game players and use motion-sensing interaction technology to control 3D character models in VR. A similar study (8) showed the construction of a geometric VR platform for environmental navigation, where non-panoramic photos and wearable electronics with Bluetooth wireless transmission functions were used to combine the user's actions with the VR environment in a first-person VR platform.…”
Section: Functional Tests and Experiments Resultsmentioning
confidence: 99%
“…The purpose of this study was to construct a treasure hunt game script in an ancient Chinese virtual reality (VR) (8)(9)(10) environment by combining VR and wearable devices. Research motivations included (1) to demonstrate the potential of the ATmega168 core chip and sensors, such as a three-axis accelerometer and gyroscopic sensor, which are incorporated into a watch-type wearable device that can detect forward, left-turning, and right-turning actions of game players and whose functions are similar to those of the Mi Band; (2) to study the technology that the Unity game engine uses to control objects in VR and establish a new milestone for window animation in a human-machine interface; and (3) to cultivate the capabilities of a motion-sensing interactive multimedia device, focusing in particular on enhancing the functions of the wireless transferring module to make future cloud processing possible.…”
Section: Introductionmentioning
confidence: 99%
“…A virtual sphere with a high immersion of engagement calls for the roles of the designer in designing the virtual world environment (Welty & Setiawan, 2019). VR, which is highly related to computer technology because of the picture quality and 3D, contributes to the sensory efficacy that depends on computational speed (Hu et al, 2018). The rapid development of science and technology accelerate the perfection and popularity of VR, making the use of VR expand to various fields (Hu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…VR, which is highly related to computer technology because of the picture quality and 3D, contributes to the sensory efficacy that depends on computational speed (Hu et al, 2018). The rapid development of science and technology accelerate the perfection and popularity of VR, making the use of VR expand to various fields (Hu et al, 2018). The claim refers to how VR is diversely applied to military practice, healthcare, education, manufacture, entertainment (McGlynn et al, 2018), advertising, architecture, professional simulation (Hu et al, 2018) environmental navigation, like maps (Hu et al, 2018), and psychological research (Diemer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation